Experiences with insecticide-treated curtains: a qualitative study in Iquitos, Peru. (December 2016) - Paz-Soldan, Valerie; Bauer, Karin; Lenhart, Audrey; Cordova Lopez, Jhonny; Elder, John; Scott, Thomas; McCall, Philip; Kochel, Tadeusz; Morrison, Amy
Abstract Background Dengue is an arthropod-borne viral disease responsible for approximately 400 million infections annually; the only available method of prevention is vector control. It has been previously demonstrated that insecticide treated curtains (ITCs) can lower dengue vector infestations in and around houses. As part of a larger trial examining whether ITCs could reduce dengue transmission in Iquitos, Peru, the objective of this study was to characterize the participants' experience with the ITCs using qualitative methods. Methods Knowledge, attitudes, and practices (KAP) surveys (at baseline, and 9 and 27 months post-ITC distribution, withn = 593, 595 and 511, respectively), focus group discussions (at 6 and 12 months post-ITC distribution, withn = 18 and 33, respectively), and 11 one-on-one interviews (at 12 months post-distribution) were conducted with 605 participants who received ITCs as part of a cluster-randomized trial. Results Focus groups at 6 months post-ITC distribution revealed that individuals had observed their ITCs to function for approximately 3 months, after which they reported the ITCs were no longer working. Follow up revealed that the ITCs required re-treatment with insecticide at approximately 1 year post-distribution. Over half (55.3 %, n = 329) of participants at 9 months post-ITC distribution and over a third (34.8 %, n = 177) at 27 months post-ITC distribution reported perceiving a decrease in the number of mosquitoes in their home. The percentage of participants who would recommend ITCs to their family or friends in the future remained high throughout the study (94.3 %, n = 561 at 9 months and 94.6 %, n = 488 at 27 months post-distribution). When asked why, participants reported that ITCs were effective at reducing mosquitoes (81.6 and 37.8 %, at 9 and 27 months respectively), that they prevent dengue (5.7 and 51.2 %, at 9 and 27 months), that they are "beautiful " (5.9 and 3.1 %), as well as other reasons (6.9 and 2.5 %). Conclusion ITCs have substantial potential for long term dengue vector control because they are liked by users, both for their perceived effectiveness and for aesthetic reasons, and because they require little proactive behavioral effort on the part of the users. Our results highlight the importance of gathering process (as opposed to outcome) data during vector control studies, without which researchers would not have become aware that the ITCs had lost effectiveness early in the trial.